(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The growth of cancer from the colon or rectum is referred to as colorectal cancer (CRC), sometimes known as bowel cancer, colon cancer, or rectal cancer. It is the third most prevalent disease in women and the fourth most common cancer in men worldwide. Colorectal Cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. More recently, nanomedicine has emerged as an attractive modality to overcome issues of therapeutic resistance, improper delivery, or suboptimal targeting of tumor cells. Around 50 nano-formulations have so far been approved as diagnostic and therapeutic agents in humans. One of the most promising methods for cancer treatment is the use of nanoparticles as a drug delivery mechanism. Targeted nanoparticles could take use of chemicals that are differentially expressed on the surface of tumour cells to deliver deadly medicines effectively. Recent research has shown that different compounds can act as ligands on nanoparticle surfaces to engage with tumour cells and facilitate the delivery of anticancer medicines. Here, we examine the intriguing utilisation of ligands and cellular targets in potential CRC therapeutic options and show recent developments in targeted nanoparticles against CRC.